Proceedings of the 6th ACM SIGCOMM Conference on Internet Measurement 2006
DOI: 10.1145/1177080.1177101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of packet sampling on anomaly detection metrics

Abstract: Packet sampling methods such as Cisco's NetFlow are widely employed by large networks to reduce the amount of traffic data measured. A key problem with packet sampling is that it is inherently a lossy process, discarding (potentially useful) information. In this paper, we empirically evaluate the impact of sampling on anomaly detection metrics. Starting with unsampled flow records collected during the Blaster worm outbreak, we reconstruct the underlying packet trace and simulate packet sampling at increasing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(135 citation statements)
references
References 20 publications
3
132
0
Order By: Relevance
“…Androulidakis et al [55] show that systematic sampling is especially problematic when the detection algorithms depend on the observation of a particular packet (e.g., SYN flag). Brauckhoff et al [56] also find that some anomaly detection metrics are more resilient to sampling than others, especially those based on entropy summarizations, and that detection algorithms based on packet and byte counts are less affected than those based on flow counts.…”
Section: Related Workmentioning
confidence: 99%
“…Androulidakis et al [55] show that systematic sampling is especially problematic when the detection algorithms depend on the observation of a particular packet (e.g., SYN flag). Brauckhoff et al [56] also find that some anomaly detection metrics are more resilient to sampling than others, especially those based on entropy summarizations, and that detection algorithms based on packet and byte counts are less affected than those based on flow counts.…”
Section: Related Workmentioning
confidence: 99%
“…Several state-of-the-art tools require access to packet payloads, which renders these solutions impractical for this environment. Recent studies [5][6][7] have shown that the accuracy of certain anomaly detection techniques is dramatically affected under sampling.…”
Section: Sampled Netflow Supportmentioning
confidence: 99%
“…This confirms our hypothesis that conditional entropy, capturing dependence between feature pairs, could be a more useful statistic in detecting anomalies. Empirical entropy applied to monitoring of network traffic has been shown to be very useful in detecting changes in its character, as first suggested in [18] and then developed in [17] and other works (e.g., [4], [10], [16], [19], [21], [22]). While possessing the significant advantage of needing few modeling assumptions about what constitutes normal and abnormal traffic, entropy-based methods incur substantial computational cost, which presented an obstacle to their practical adoption.…”
Section: B Detecting Attacks With Conditional Entropymentioning
confidence: 99%
“…The information-theoretic statistic of empirical entropy (or simply entropy) has received a lot of attention in this respect [4], [10], [16], [17], [18], [19], [21], [22]. Computing entropy in the straightforward manner, by maintaining counters to keep track of the distribution histogram, is expensive memory-wise and computationally.…”
Section: Introductionmentioning
confidence: 99%